RETROSPECTIVE EVULATION OF DEMOGRAPHIC AND CLINICAL CHARACTERISTICS OF PATIENTS WITH BURNING MOUTH SYNDROME - ERÇALIK YALÇINKAYA, ŞEBNEM (My University, 2022)
Burning Mouth Syndrome (BMS) is chronic pain and burning sensation in the mouth accompanied by various symptoms mainly seen in peri- and postmenopausal women. Burning and stinging sensation on the tongue, lips and other oral mucosal surfaces, dry mouth or increased salivation, taste change, loss of taste, and paresthesia are the prominent symptoms. In this study, it was aimed to evaluate the demographic and clinical characteristics of BMS patients. The records of BMS patients were retrospectively retrieved from the archive of Marmara University, Faculty of Dentistry, Outpatient Clinic of Department of Oral and Maxillofacial Radiology. Patients’ data were further searched into the faculty database. Patients were classified according to the intensity of pain and burning complaints during the day. Data were evaluated with descriptive statistical analysis and chi-square tests. The significance level was determined as p<0,05. A total of 50 patients were deemed fit to the criteria. It was found that the majority of BMS patients were female (%76, n=38; mean age=58,4±13 years) and BMS was more frequent in females (p<0,05). Type 2 (Burning feeling that continues throughout the day) was determined as the most prevalent type of BMS (%52, n=26). The findings of the study showed that the most frequent type of BMS was Type 2 and it was more frequently seen in women. Its etiopathogenesis has not been clarified and since it may be idiopathic, the patients should be carefully evaluated. Individual treatment methods are needed whilst determining the treatment plan. Dental clinicians should take into consideration the possible peak periods while examining and treating BMS patients.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); burning mouth; dry mouth; oral dysesthseia